Вербування та експлуатація дівчат під час збройних конфліктів (досвід Донбасу) - Клименко, Олена; Klymenko, Elena (Волинський національний університет імені Лесі Українки, 2020)
Мета статті – вивчення проблеми залучення дітей до участі у військових конфліктах й аналіз досвіду Донбасу в питанні вербування дівчат до незаконних збройних формувань та їх опосередкованої участі (експлуатації військовими) в позабойовому житті. Оскільки ця проблема недостатньо досліджена, зроблено спробу аналізу добровільних і примусових форм вербування дівчат, ролі в цьому пропаганди в ЗМІ, соціальних та Інтернет-мереж, а також учителів загальноосвітніх шкіл і безпосередньо батьків. Окремо проведено аналіз факторів, що сприяють залученню дівчат як специфічної гендерної групи до участі в діяльності незаконних збройних формувань. Особливу увагу приділено висвітленню факторів соціального відчуження та тяжіння в рамках негативної взаємодії, а також вивченню особистісних і групових мотивів приєднання дівчат до незаконних збройних угрупувань. Окремо досліджено роль віртуальної взаємодії в процесі вербування. The purpose of the article is to study the problem of attracting children to participate in military conflicts, as well as to analyze the experience of Donbass in the issue of involving girls in the activities of illegal armed formations and their indirect participation (exploitation by the military) outside of combat life. Since this problem has not been sufficiently studied by the author, an attempt was made to analyze voluntary and compulsory forms of recruiting girls and the role of propaganda in the media, social and Internet networks, as well as teachers of secondary schools and parents directly in this. A separate analysis of the factors contributing to the attraction of girls, as a specific gender group, to participate in the activities of illegal armed groups is carried out. Particular attention is paid to highlighting the role of factors of social alienation and attraction in the framework of the negative experience of social interaction, in addition, the personal and group motives of girls joining illegal armed groups are studied. A key role in the formation of strategies for attracting girls to join military-patriotic clubs and armed groups in the Donbas is the determination of the individual characteristics of social interaction carried out by a child. The experience of negative social interaction with the immediate environment plays a fundamental role in the process of accepting consent. That is why the article analyzes the dependence of the choice of recruitment strategies for adolescent girls on the factors of social alienation and attraction of those present in their lives. Цель статьи – изучение проблемы привлечения детей к участию в военных конфликтах, а также анализ опыта Донбасса в вопросе вовлечения девушек в деятельность незаконных вооруженных формирований и опосредованное их участие (эксплуатации военными) во внебоевой жизни. Поскольку данная проблема недостаточно исследована, нами предпринята попытка анализа добровольных и принудительных форм вербовки девушек и роли в этом пропаганды в СМИ, социальных и Интернет-сетей, а также учителей общеобразовательных школ и непосредственно родителей. Отдельно проводится анализ факторов, способствующих привлечению девушек как специфической гендерной группы к участию в деятельности незаконных вооруженных формирований. Особое внимание уделяется освещению роли факторов социального отчуждения и притяжения в рамках негативного опыта социального взаимодействия, кроме того, изучены личностные и групповые мотивы вступления девушек в незаконные вооруженные группировки. Ключевую роль при формировании стратегий привлечения девушек к вступлению в военно-патриотические клубы и вооруженные группировки на Донбассе играет определение индивидуальных особенностей социального взаимодействия, осуществляемого ребенком. Фундаментальную роль в процессе принятия согласия играет опыт негативного социального взаимодействия с ближайшим окружением. Именно поэтому в статье анализируется зависимость выбора стратегий вербовки девочек-подростков от факторов социального отчуждения и притяжения, присутствующих в их жизни.
Recruitment and Exploitation of Girls During Armed Conflicts (Donbass Experience).
Keywords: діти; дівчата; збройний конфлікт; вербування; експлуатація; незаконні збройні формування; children; girls; armed conflict; recruitment; exploitation; illegal armed groups; дети; девушки; вооруженный конфликт; вербовка; эксплуатация; незаконные вооруженные формирования; 316.346.32